Cognitive Stylistics in Wordsworth’s The Solitary Reaper: Mental Simulation and Conceptual Blending - Saputra, Diendra Wahyu; Siregar, Lailan Haz; Septiandri, Rizky; Taufany, Wahyu; Rangkuti, Rahmadsyah (Universitas Pahlawan Tuanku Tambusai, 2025)
The study of cognitive stylistics has become increasingly significant in understanding how readers engage with literary texts, particularly poetry. Despite existing research, there remains a gap in examining mental simulation and conceptual blending specifically in William Wordsworth’s The Solitary Reaper. This study aims to explore these cognitive processes and their impact on emotional engagement with the poem. Utilizing a qualitative descriptive analytical approach, we conducted a close reading of the text, supported by relevant literature on cognitive stylistics. Our findings indicate that Wordsworth’s vivid imagery and emotional resonance facilitate mental simulation, allowing readers to connect deeply with the themes of solitude and beauty. Additionally, conceptual blending merges various emotional and contextual elements, enhancing the poem’s interpretative richness. This research highlights the role of cognitive stylistics in appreciating poetry and how language activates cognitive and emotional responses.